Concept WIND in the Texts of Ukrainian Folk Orders - Шуляк, Світлана Андріївна (Київський національний університет імені Тараса Шевченка, 2018)
The essence of the concept WIND is invetigated in the article in the texts of Ukrainian folk orders. The peculiarities of expression and functioning of this concept in orders of different thematic groups are determined. The linguistic means, which form the semantic content of the concept WIND, are described. The language model of the world, reflecting the peculiarities of a certain lingoculture, retains the perceptions inherent to the society. One of the key concepts of Ukrainian ethnoculture is the wind energy, which implements universal and national specifics. Concept WIND is a fragment of the language model of the world of Ukrainians; it preserves the results of cognitive activity and reflects archetypal representations of the mental model. Emotional assessment of the wind in the texts of Ukrainian orders is ambivalent. On the one hand, the wind is conceived as an assistant, and on the other hand – as a dangerous, unmanageable power. For the most part, the concept WIND is verbalized in the texts of orders from pains, from the bite of a snake, and its metaphorical transformations are manifested by epithets that depict sad images. The lexeme wind is associated with the persistent character of the violent. Epithets strong, violent specify the semantics of the wind. Constituents of the concept WIND are tokens on the designation of motion, time and space. In the texts of Ukrainian folk orders the token is accompanied by a number of symbols. Personification of the wind is realized in the appeals, illustrating the connection with the mythical knowledge of our ancestors. Appeal to the wind is an integral part of the spell formula, which manifests itself in the acts of a request, requirement or order. The formula for the protection or prevention is order, in which there are verbs with "guarding" semantics, such as: help, save, and protect. The formulation of the submission is made using the verb in the orderly manner and the circumstances of the place, it is productive in orders, where the disease is sent by the wind and by the smoke. The verbal formulas of the texts of the Ukrainian folk orders, in which the concept WIND operates, reflects the model of the Ukrainian’s world. Orders are an exceptionally important component of the folk medicine of Ukrainians and are among the suggestive means of treating the patient's mental and physical disorders.

У статті досліджено функціонування концепту ВІТЕР у текстах українських народних замовлянь. Визначено особливості вираження та функціонування цього концепту в замовляннях різних тематичних груп. Охарактеризовано мовні засоби, якими формується семантичне наповнення концепту ВІТЕР. Мовна картина світу, віддзеркалюючи особливості певної лінгвокультури, зберігає уявлення, які притаманні суспільству. Одним із ключових концептів української етнокультури є лексема вітер, у якій реалізується універсальна та національна специфіка. Концепт ВІТЕР становить фрагмент мовної картини світу українців, зберігає результати пізнавальної діяльності, віддзеркалює архетипні уявлення ментальної моделі. Емоційна оцінка вітру в текстах українських замовлянь є амбівалентною. З одного боку, вітер осмислюється як помічник, а з іншого – як небезпечна, некерована сила. Здебільшого концепт ВІТЕР вербалізується в текстах замовлянь від болю, від укусу змії, а його метафоричні особливості маркуються епітетами, що малюють сумні образи. Лексема вітер асоціюється з постійною характерологічною ознакою буйний. Епітети злетворний, буйний конкретизують, уточнюють семантику вітру. Вербалізаторами концепту ВІТЕР є лексеми на позначення руху, часу і простору. У текстах українських народних замовлянь лексему вітер супроводжує числова символіка. Персоніфікація вітру реалізується у звертаннях, ілюструючи зв’язок з міфопоетичною свідомістю наших предків. Звертання до вітру є невід’ємним елементом формули заклинання, яка проявляється в актах прохання, вимоги чи наказу. Формулу оберігання або недопущення представляють замовляння, в яких поряд з лексемою вітер присутні дієслова з «охоронною» семантикою, як-от: спаси, сохрани, охороняйте. Формула відсилання утворена за допомогою дієслова у наказовому способі та обставини місця і є продуктивною у замовляннях, де хворобу відсилають за вітром і за димом. Словесні формули текстів українських народних замовлянь, у яких функціонує концепт ВІТЕР, відображають картину світу нашого народу. Замовляння виступають винятково важливим компонентом народної медицини українців і належать до сугестивних засобів лікування психічного і фізичного стану хворого.
Концепт ВІТЕР у текстах українських народних замовлянь
Keywords: Ukrainian folk orders; text; concept WIND; language model of the world; ambivalence; symbol; mimicry; semantics; lexeme; українські народні замовляння; текст; концепт ВІТЕР; мовна картина світу; амбівалентність; символ; міфочисла; семантика; лексема